(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In the article the problem of the status of value as life-meaning intention of human being, its ratios with such manifestations of human spirit as aspirations, motivations and the purposes is considered. This issue, it is thought, isn’t understood enough. After all there are essential distinctions in understanding of the nature of values. The value sense as the general basis finds its expression in contents of more concrete motives. Motives, being means of their expression, are closer to forms of being manifestation. Valuable sense, being differentiated in different types of motives receives even more certain specification in purposes of individuals. The purposes, reaching the result, can become final. In purposes deep sense finds its being outline, being expressed in various forms of a discourse – in language, behavior, ways of activity and communication, methods and approaches, and at last, in the common collateral results in which concreteness of separate culture is presented.